Advanced Combustion and Aerothermal Technologies Environmental Protection and Pollution Reductions - Syred, Nick; Khalatov, Artem (NATO Science for Peace and Security Series C: Environmental Security, 2007)
The NATO Advanced Workshop "Advanced Combustion and Aerothermal Technologies: Environmental Protection and Pollution Reductions" was held in Kiev (Ukraine) from 15 to 19 May 2006 and was organized by the Institute of Engineering Thermophysics (Ukraine) and Cardiff University (UK). This Workshop based on the long-term collaboration between the Institute of Engineering Thermophysics and Cardiff University resulted in a first NATO Scientific Prize received by Professor N. Syred, UK, and Professor A. Khalatov in 2002, who served as Workshop codirectors. The justification for this Workshop was based upon the perceived need for the bringing together of research in a number of combustion and aerotherm- related areas, so as to allow more rapid progress to be made. The primary Workshop objectives were to assess the existing knowledge on advanced combustion and aerothermal technologies providing reduced environmental impact, to identify directions for future research in the field, and to promote the close relationships and business contacts between scientists from the NATO and partner countries. This synergy in research and development is essential if advances in specific areas are to be widely utilized, whilst helping to cro- fertilize other areas and stimulate new developments. Of especial importance is the dissemination of concepts and ideas evolved in the aerospace industries into other related areas, whilst encouraging contacts, research exchanges, and int- actions between engineers and scientists in the NATO and partner countries.